DETERMINATION OF VOLUME AND DIRECTION OF FLOW OF KAINJI RESERVOIR USING HYDRO-GEOMATICS TECHNIQUES (Nigerian Journal of Technology, 2017)
Determination of volume and direction of flow of river plays a key role in determining the direction of transported materials to the downstream. Bathymetry survey which incorporate sounding to determine the depths with respect to a known bench mark together with coordinates of points referenced to a minimum of two horizontal controls are enough to fix position of points aboard a boat traversing a river during field work. In this paper, MIDAS Echo Sounder and Trimble Dual Frequency GPS was used for data acquisition. Data analysis was done with the aid of Surfer golden software. The results obtained showed a computed volume of 13200456.595Mm3,13226766.629Mm3 and 13209519.223Mm3for the reservoir using trapezoidal, Simpson’s and Simpson’s 3/8 rules respectively. A contour map, 3D wireframe map overlaid with grid vector maps of the river bed were produced to create a 3D effect of Kainji reservoir flow direction. A depth of 23.50m was obtained during the sounding field operation. http://dx.doi.org/10.4314/njt.v36i4.3